2012
DOI: 10.4999/uhod.10064
|View full text |Cite
|
Sign up to set email alerts
|

JAK 2V617F Mutation: Frequency and Relation to Clinical and Laboratory Features of BCR-ABL Negative Myeloproliferative Diseases

Abstract: In this study, we planned to investigate frequency of the JAK2 V617F mutation and it's relation with clinical and laboratory findings of BCR-ABL negative myeloproliferative diseases (MPD) which consist of polycythemia vera (PV), essential thrombocythemia (ET) and idiopathic myelofibrosis (IMF). Totally 65 patients were included in the study which composed of 28 (43.1 %) PV, 29 (44 %) ET and 8 (12.3 %) IMF patients. Forty one (63%) patients were female and 24 (37%) were male. Mean age of patients was 64.02±12.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
0
1
Order By: Relevance
“…The present study revealed that the mean age of incidence in Sudanese patients with polycythaemia Vera was in the fourth decade and this finding disagrees with findings from a study done by Sazawal et al, (2010) in India which reported that mean age of incidence of polycythaemia Vera is in the fifth decade. Also the present study disagrees with study done in India (Karakus, 2012) which reported that Median age at diagnosis was 60 years. In agreement with the fact that polycythaemia Vera was not reported in patients under 20 years old, none of our patients was aged less than 20 years.…”
Section: Discussioncontrasting
confidence: 99%
“…The present study revealed that the mean age of incidence in Sudanese patients with polycythaemia Vera was in the fourth decade and this finding disagrees with findings from a study done by Sazawal et al, (2010) in India which reported that mean age of incidence of polycythaemia Vera is in the fifth decade. Also the present study disagrees with study done in India (Karakus, 2012) which reported that Median age at diagnosis was 60 years. In agreement with the fact that polycythaemia Vera was not reported in patients under 20 years old, none of our patients was aged less than 20 years.…”
Section: Discussioncontrasting
confidence: 99%